Efektivitas Peran Lembaga Pemasyarakatan Maximum Security dalam Upaya Pembinaan Narapidana di Lembaga Pemasyarakatan Khusus Kelas Iia Gunung Sindur - Riki Bramandita; Dian Eka Prastiwi (Departement of Mathematics Education, 2023)
The research aims to: 1) understand and analyze the effectiveness of the role of maximum security penitentiary in the convict coaching at Special Class IIA Gunung Sindur Penitentiary; 2) understand and analyze the inhibiting factors in the convict coaching at Special Class IIA Gunung Sindur Penitentiary. The research was conducted in April - June 2020 by juridical and empirical approach. The respondents were consist of prisoners and penitentiary officer selected by the snowball method. The research showed that the role of Special Class IIA Gunung Sindur Penitentiary with maximum security in the convict coaching has not been effective based on Republic of Indonesia Law Number 12 of 1995. Inhibiting factors include the limited number of trained corectional officers, the Penitentiary layout is not in accordance with the need for convict coaching, coaching methods have not been updated, the stages of coaching program are not sustainable, the roles of related agencies are not harmonious and sustainable, lack of training time, and lack of interest from prisoners in the coaching program.